Ways of denoting characteristics through domestic animal metaphor in English - Hồ, Thị Thu Trang (ĐHNN, 2017)
The thesis investigates different ways of denoting human character traits through some domestic animal metaphors in English, i.e. Dog, Cat, Chicken, Pig, and Cow. It also attempts to explore the reasons underlying the association of these domestic animals’ ascribed attributes with some salient human character traits. Data for the analysis have been gathered mainly from English dictionaries and corpora. Some Vietnamese instances taken from online sources are also included, serving as illustrations of how these domestic animal are conceptualized in Vietnamese language, but a deeper contrastive analysis of domestic animal metaphors between the two languages is by no means within the scope of the study. The collected linguistic data are then grouped and analyzed according to the character traits that they represent. A total of 13 character traits have been discussed in the thesis and the most prominent character traits associated with Dog, Cat, Chicken, Pig and Cow are summarized. At the end of the thesis, teaching implications as well as some suggestions for translating texts concerning animal metaphor are also included.